Novel Locus for Generalized Epilepsy with Febrile Seizures Plus - J Gordon Millichap (Pediatric Neurology Briefs)
Linkage analysis was conducted in 5 French families with generalized epilepsy with febrile seizures plus (GEFS+), with at least 7 affected members with autosomal dominant transmission, in an attempt to localize a new gene for GEFS+, at Hospitalier Pitie-Salpetriere, Paris, France.